Inhibition of interferon, cytokine, and lymphocyte proliferative responses in elite swimmers with altitude exposure - Pyne, D. V.; McDonald, W. A.; Morton, D. S.; Swigget, J. P.; Foster, M.; Sonnenfeld, G.; Smith, J. A. (Journal of Interferon & Cytokine Research, 2000)
To determine the immunologic consequences of athletic training at altitude, blood samples were taken at rest from 10 swimmers and 8 control nontraining but altitude-exposed members of the 1996 Australian Olympic Swimming Team, near the start and completion of a 21-day training camp at 2102 m. Blood leukocyte numbers dropped in both groups (p < 0.05), with the decrease greater in the swimmers (-38% swimmers, -3% controls). Concanavalin A (ConA)-induced blastogenesis decreased in both groups (p < 0.01), but the drop was greater in the control group (-32% swimmers, -56% controls, p < 0.05). Lipopolysaccharide (LPS)-induced blastogenesis more than doubled in both groups (281% swimmers, 249% controls, p < 0.01). Increases in mitogen-induced interleukin-1beta (IL-1beta), IL-4, and interferon-gamma (IFN-gamma) production and a decrease in IL-2 levels were observed in both groups after altitude exposure (all p < 0.05). The percentage of cells expressing HLA-DR fell (-33% swimmers, -20% controls, p < 0.01), whereas those expressing CD-4 expression increased (16% swimmers only, p < 0.01). Although training at medium-level altitude alters some immunologic parameters, the training-induced changes may be secondary to those induced by altitude alone.